(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article describes the essence of economic liberalization, theoretical and practical measures to ensure economic freedom in a market economy, the strategy of developed countries in liberalization and the stages of introduction of economic liberalization in Uzbekistan today, the pros and cons.